A Multivariate Analysis of Incarceration and Sentence Length Decisions for Older Defendants. (August 2019) - Freiburger, Tina L.; Jordan, Kareem L.; Hilinski-Rosick, Carly M.
This study examines sentencing decisions for older defendants, and how legal and extralegal variables differently affect older defendants. Using data from the Pennsylvania Commission on Sentencing, the results indicate that defendants above the age of 50 are less likely to be sentenced to prison and jail and are more likely to be sentenced to a community sanction. For sentence length, however, those aged 50 and above receive significant longer jail sentences than those aged 18 to 29 and longer prison sentences than both those aged 30 to 49 and 18 to 29. The results also indicate that offense severity and prior record have a more negative effect on older defendants during the incarceration decision. During the sentence length decision, however, the opposite is found for the effect of offense severity. These findings are discussed and are used to make suggestions for future research and policy implications.